The Relationship between Digital Leadership of School Administrators and Learning Organization of Private Schools under Buriram Provincial Educational Office - Hengyodmak, Munee; Deepu, Sanrudee (STOU Education Journal, 2025)
The purpose of this study was to study level and relationship between the digital leadership of private school administrator and learning organization of private school under Buriram Provincial Educational Office. There were 291 samples selected from administrators and teachers of private schools under Buriram Provincial Educational Office in the academic year 2023. The research instruments were rating scale questionnaires. The digital leadership of private school administrator questionnaire with reliability .97 and the learning organization of private school questionnaire with reliability .96. Data were analyzed by frequency, percentage, mean, standard deviation, and Pearson’s product-moment correlation coefficient (r). The research result found that. 1) The organization culture of private schools under Buriram Provincial Educational Office in overall was high level. When considering each aspect were found that all aspect at high level, ordered by mean were the digital communication, digital literacy and skills, digital professional, digital vision and the digital supports in administration respectively. 2)The learning organization of private schools under Buriram Provincial Educational Office in overall was high level. When considering each aspect were found that the personal mastery empowerment was the highest level and other aspect were high level, ordered by mean were the shared vision, system thinking, learning culture, knowledge management and the technology application respectively. 3) The relationship between the digital leadership of school administrators and learning organization of private schools under Buriram Provincial Educational Office in overall was positively correlated with statistically significant at .01. The correlated coefficient was .89.